Controlled growth of silicon nanocrystallites in silicon oxide matrix using 150 MeV Ag ion irradiation - Chaudhari, P. S.; Bhave, T. M.; Pasricha, R.; Singh, F.; Kanjilal, D.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2005)
We report the synthesis of silicon nanocrystals grown in silicon oxide matrix by swift heavy ion irradiation. Thin films of silicon oxide (SiO(x)) are irradiated with 150 MeV silver ions at fluence varying from 5 x 10(11) to 1 x 10(13) ions/cm(2). The variation in the properties of silicon nanocrystals embedded in silicon oxide with varying fluence is studied. The energy of the photoluminescence peak corresponding to the silicon nanocrystals is found to be red shifted with increasing fluence. The trends in the broadening of the X-ray diffraction peak with decreasing fluence supports the controlled growth of silicon nanocrystals in silicon oxide matrix. The crystallite size of nanoclusters of silicon is seen to increase with increasing fluence. The results are discussed in view of the structural transformation, in SiO(x) matrix, caused by swift heavy ion irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oxide matrix; silicon nanocrystallites; swift heavy ion irradiation

Oriented growth of nanocrystalline gamma ferric oxide in electrophoretically deposited films - Bhave, T. M.; Balasubramanian, C.; Nagar, H.; Kulkarni, S.; Pasricha, R.; Bakare, P. P.; Date, Sadgopal K.; Bhoraskar, S. V. (Hyperfine Interactions, 2005)
Films of nanocrystalline gamma-Fe2O3 were deposited on silicon substrates by using the technique of electrophoretic deposition. The precursor powder was nanocrystalline gamma-Fe2O3, which was synthesized, using DC arc plasma in the oxygen ambient by vapour-vapour interaction in gas phase condensation; at a stabilized arc current of 40 A. This powder was characterized by X-ray diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and Mossbauer Spectroscopy. An increase in directional coercivity was observed in case of films deposited on silicon substrates, which is dramatically significant. Preferred orientation of almost similar sized nanocrystalline magnetic domains in deposited films is evident from the results of X-ray diffraction and Transmission Electron Microscopy results. The preferred alignment of the nanocrystallites seems to be responsible for the significant changes observed in magnetic properties of films.